Learning by joining the rhythm. Apprenticeship learning in elite double sculls rowing - Lund, O.; Ravn, S.; Christensen, M. K. (Scandinavian Sport Studies Forum, 2012)
This article aims to explore how a joint rhythm is learned. The exploration is based on a combination of a case study of training in elite rowing and theoretical considerations concerning mutual incorporation of skills in learning. In 2009 Juliane and Anne start to row the double scull together. The two rowers` aim is to be among the exclusive group of teams that qualify for the Olympic Games three years later. However, Anne is not a rower, and has to be apprenticed by Juliane, who is an experienced elite rower. One important learning goal in the apprenticeship is to find a good joint rhythm, which will enable the rowers to put optimal effort into the rowing. Thus the apprenticeship is about developing a sense for a good rhythm in Anne which corresponds to Juliane`s finely tuned sense of what a good rhythm should feel like. Our study suggests that apprenticeship learning has to be understood as an embodied and mutually affecting process rather than as unidirectional exchanges of information. This means that not only the inexperienced athlete is learning: the experienced athlete is also learning by compensating for the inexperienced athlete`s inadequacy.